Metapolitefsi: From the Transition to Democracy to the Economic Crisis, Athens, 14–16 December 2012 - Giannakopoulos, Georgios (Historein, 2013)
The conference on “Metapolitefsi: From the Transition to Democracy to the Economic Crisis”, organised by Historein in collaboration with the Free University of Berlin and held in Athens on 14–16 December 2012, sought to offer a first systematic account of the historical period from the fall of the Greek military dictatorship (1974) to the recent economic crisis. This postauthoritarian period in Greek politics and society is frequently referred to as the metapolitefsi.